2020
DOI: 10.3390/en13112847
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Welded Plate Heat Exchanger for Ammonia Synthesis Column: An Experimental Study with Mathematical Optimisation

Abstract: The production of ammonia, consuming up to 5% of natural gas global production, accounts for about 2% of world energy. Worldwide, the Haber–Bosch process is the mainly used method of ammonia catalytic synthesis, involving temperatures up to 600 °C and pressures up to 32 MPa. In this paper, the results of the development and study of the special welded construction of plate heat exchanger (WPHE) for a column of ammonia synthesis are presented. The heat transfer and hydraulic performance of developed WPHE are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The main technical route of this project is to use the clean electric energy of photovoltaic power plants to electrolyze water to produce hydrogen and then combine hydrogen and enriched carbon dioxide to produce methanol. The project plans to construct an annual output of 1,000 tons of methanol, about 1500 tons of carbon dioxide, and an annual demand of about 200 tons of hydrogen [21].…”
Section: Fig 6: Flow Chart Of Low-temperature Power-to-methanol (Adopted From [34])mentioning
confidence: 99%
“…The main technical route of this project is to use the clean electric energy of photovoltaic power plants to electrolyze water to produce hydrogen and then combine hydrogen and enriched carbon dioxide to produce methanol. The project plans to construct an annual output of 1,000 tons of methanol, about 1500 tons of carbon dioxide, and an annual demand of about 200 tons of hydrogen [21].…”
Section: Fig 6: Flow Chart Of Low-temperature Power-to-methanol (Adopted From [34])mentioning
confidence: 99%
“…In Northern China, for example, this amounts to 100 Mt standard coal equivalents (Mtce, 2.93 EJ) and throughout steel mills in Hebei province it reaches 44,268 MW and in cement factories 2155 MW [51]. These issues were addressed by several papers in the SI, e.g., [52].…”
Section: Emerging Toolsmentioning
confidence: 99%
“…Reactors with built-in heat recovery systems are most commonly used for traditional ammonia synthesis [118], in which hot reaction products heat the reactants to the required temperature. The authors of the final paper in this theme, Tovazhnyanskyy et al [52], reported on "Optimal Design of Welded Plate Heat Exchanger for Ammonia Synthesis Column: An Experimental Study with Mathematical Optimisation". They investigated heat transfer in a plate heat exchanger with a specially welded construction for use in ammonia synthesis.…”
Section: Integrated and Newly Developed Heat Exchangersmentioning
confidence: 99%
“…An exchanger efficiency study aimed at applications in the dairy industry was presented in [17]. Mathematical optimization for PHEs applied to the ammonia production industry in [18]. Alam and Kim [19] proposed a graphical method and rules to integrate the heat exchanger network, considering the pressure variation in the distillation columns.…”
Section: Introductionmentioning
confidence: 99%